Extensive pollen flow in a natural fragmented population of Patagonian cypress Austrocedrus chilensis - Colabella, Fernando (2014)
Habitat fragmentation might significantly affect mating and pollen dispersal patterns in plant populations, contributing to the decline of remnant populations. However, wind-pollinated species are able to disperse pollen at longer distances after opening of the canopy. Our objectives were to characterize the mating system parameters and to estimate the average distance of effective pollen dispersal in the wind-pollinated conifer Austrocedrus chilensis. We sampled 19 “mother trees,” 200 progeny, and 81 additional adults (both male and female), in a fragmented population at the Argentinean Patagonian steppe. We registered the spatial positions of individuals and genotyped all samples with five microsatellite markers. We found a high genetic diversity, a moderated rate of biparental inbreeding (tm  − ts = 0.105), and a complete absence of correlated paternity (rp = −0.015). The effective number of pollen donors contributing to a single mother (Nep) was 13.9. Applying TWOGENER, we estimated a low but significant differentiation among the inferred pollen pools (ΦFT = 0.036, p = 0.001) and a very large average pollen dispersal distance (d = 1,032.3 m). The leptokurtic distribution (b = 0.18) presumes a potential for even larger dispersal distances. The high genetic diversity, the mating patterns, and the extensive pollen dispersal presume that habitat fragmentation did not have a negative impact on pollen movement in this population of A. chilensis. Genetic connectivity among fragmented populations scattered in the Patagonian region is possible, and we stress the need of management policies at the landscape level.